Utilization of ANC and PNC Services in Nepal: A Multivariate Analysis Based on Nepal Demographic Health Survey 2001 and 2006. - Mahara, G.; Asweto, Collins O.; Cao, K.; Alzain, M. A.; Sebastian, A.; Barr, J.; Guo, X.; Wei, W. (Science Publishing Group, 2015)
Background: Maternal Mortality is a public health problem in Nepal, which was highest in 1990 among the South Asian countries. Associated factors of maternal mortality are various; among them maternal health services such as antenatal (ANC) and postnatal care (PNC) services are the main. Methods: A multivariate secondary data analysis out based on Nepal Demographic Health Surveys 2001 and 2006. Logistic regression models was performed to compare the utilization of the ANC and PNC services, with background characteristics of women aged between 15 to 49 years old. Results: A total of 8913 reproductive aged groups (15-49) women were taken for analysis and the mean age was 28.59±7.040 years. Logistic regression analysis revealed that health facility delivery (AOR=1.297, 95% CI=1.135-1.481), PNC check-up at health facility (AOD=4.442, 95% CI=2.815-7.011) and PNC service with a skilled health worker (AOD=4.533, 95% CI=2.753-7.465) utilized more in 2006 compared to 2001. This study also found that highly educated women had (AOD, 95% CI=10.823- 22.968) more utilized the heath facility during pregnancy and (AOD, 95% CI=2.194-16.950) more likely during a PNC checkup, whereas, educated women were less (AOR=0.043, 95% CI=0.007-0.254) likely consult with a skilled professional. Similarly, antenatal care (ANC) visits (4 or more than four) and ANC visit in the first trimester were increased (95% CI=1.137- 1.518) and (AOD=1.041, 95% CI=0.924-1.173) respectively. This study found that educated women, those who were living in urban areas, were more likely to use maternal health services compared to other regions. Conclusion: Increased in utilization of the ANC and PNC services through skilled health workers in a health facility among cohorts of educated women. However, the improvements were not equally distributed across the all regions in the country. This utilization of maternal health services is not sufficient to achieve the MDG goal. Because, health facility delivery is poor and counterpart home delivery is still high in Nepal.
Keywords: Antenatal Care and Postnatal Care; Maternal Health Service; Nepal